TINGKAT PENGETAHUAN, KETERPAPARAN INFORMASI, DAN DUKUNGAN TENAGA KESEHATAN BERHUBUNGAN DENGAN PERILAKU PEMERIKSAAN PAYUDARA KLINIS (SADANIS) PADA WANITA DI KELURAHAN BANTUL KECAMATAN BANTUL BANTUL YOGYAKARTA - Dea siskia; Intan Mutiara Putri; Fitria Siswi Utami (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
Breast cancer is a type of cancer that has the highest contribution to the prevalence of cancer in women in Indonesia. Breast cancer has a high mortality rate due to delay in early detection. Breast cancer survivors are generally detected at an advanced stage. WHO also stated that there was a significant increase in breast cancer cases, namely 1.7 million new cases every year. Indonesia has a high incidence and mortality rate due to breast cancer. This study aims to determine the correlation between the level of knowledge, exposure to information and support from health workers on Clinical Breast Examination (SADANIS) behavior in Bantul Subdistrict, Bantul District, Bantul Yogyakarta. The study employed a quantitative research design with a cross sectional approach. The number of samples was 51 respondents with the total sampling technique. The data analysis used Fisher Exact test. The results of statistical test analysis showed a significant correlation between the level of knowledge (p-value 0.027) with SADANIS behavior, information exposure (p-value 0.011) with SADANIS behavior and support from health workers (p-value 0.037) with SADANIS behavior. The conclusion of this study is that there is a relationship between knowledge and SADANIS behavior, information exposure with SADANIS behavior and support from health workers with SADANIS behavior. It is hoped that women in family welfare empowerment (PKK) organization increase awareness regarding the importance of breast cancer screening with the SADANIS method.